SISTEM INFORMASI APLIKASI "JalarCom" PADA SEKTOR PERTANIAN BERBASIS ANDROID - Nova Ameliana (2022)
ABSTRACT Technological advances are so rapid, and Indonesia is an agricultural country that produces various kinds of agricultural products, one of which is sweet potato. Sweet potato, which is easy to cultivate, is one of the agricultural products that are in demand both domestically and abroad. In a facebook group called the Sweet Potato Community (KUJ) there are approximately 32,000 members in the group, but due to the limited features available on Facebook and PT Kreasi Agro Mandiri, one of the members of the group, it is difficult to find out the location of the farmers. collectors so that it is not optimal in getting sweet potatoes. In addition, to make it easier for PT Kreasi Agro Mandiri and sweet potato business people to manage business finances, collaborate, and get information easily, the researchers built a system that can accommodate business processes for farmers, collectors and exporter. Researchers built an android-based application in which there are several menus and features, one of which is the community menu and its features are financial reports, scheduling, chat, posting and other features that will manage the JalarCom application, PT Kreasi Agro Mandiri as admin, designed using PIECES analysis. and the prototyping method of data obtained from the results of interviews.